Caffeine impairs resection during DNA break repair by reducing the levels of nucleases Sae2 and Dna2. Issue 14 (27th May 2015) - Tsabar, Michael; Eapen, Vinay V.; Mason, Jennifer M.; Memisoglu, Gonen; Waterman, David P.; Long, Marcus J.; Bishop, Douglas K.; Haber, James E.
Abstract: In response to chromosomal double-strand breaks (DSBs), eukaryotic cells activate the DNA damage checkpoint, which is orchestrated by the PI3 kinase-like protein kinases ATR and ATM (Mec1 and Tel1 in budding yeast). Following DSB formation, Mec1 and Tel1 phosphorylate histone H2A on serine 129 (known as γ-H2AX). We used caffeine to inhibit the checkpoint kinases after DSB induction. We show that prolonged phosphorylation of H2A-S129 does not require continuous Mec1 and Tel1 activity. Unexpectedly, caffeine treatment impaired homologous recombination by inhibiting 5′ to 3′ end resection, independent of Mec1 and Tel1 inhibition. Caffeine treatment led to the rapid loss, by proteasomal degradation, of both Sae2, a nuclease that plays a role in early steps of resection, and Dna2, a nuclease that facilitates one of two extensive resection pathways. Sae2's instability is evident in the absence of DNA damage. A similar loss is seen when protein synthesis is inhibited by cycloheximide. Caffeine treatment had similar effects on irradiated HeLa cells, blocking the formation of RPA and Rad51 foci that depend on 5′ to 3′ resection of broken chromosome ends. Our findings provide insight toward the use of caffeine as a DNA damage-sensitizing agent in cancer cells.